Correlation between the mechanical properties and the fiber breaking morphology of fiber reinforced shotcrete (FRS). (1st December 2021) - Zhao, Jipeng; Meng, Xiangrui; Chen, Lianjun; Liu, Guoming; Zhang, Zongxi; Xu, Qianqian
Highlights: The optimum fiber size of the PWF reinforced shotcrete is obtained. The advantages of PWF compared with PPF in shotcrete performance are determined. Four types of fiber fractures in shotcrete are proposed. The relationship between the mechanical properties of FRS and the fracture morphology of fiber is revealed. Abstract: As the primary material for roadway support in underground engineering, shotcrete is of great significance to the underground construction industry. Shotcrete alone is brittle and its internal structure is prone to damage. Thus, reinforcing materials are often added to reduce the brittleness of shotcrete. Most of the studies focused on adding fiber materials to concrete the structural fractures in shotcrete. However, shotcrete internal structure fractures still happen in extreme environments. Therefore, the relationship between the mechanical properties of fiber reinforced shotcrete (FRS) and fiber fracture morphology is studied in this paper. Firstly, two types of fibers are selected, i.e., polypropylene fiber (PPF) and plastic waste fiber (PWF). Then, the mechanical properties of the FRS are tested, and the optimal fiber size of PWF reinforced shotcrete is obtained. Through optimization analysis, the mechanical property superiority of PWF reinforced shotcrete with the optimal fiber size is determined. Next, the fiber fracture in shotcrete is observed by visual and microscopic inspection, and four types of fiber fractures in shotcrete are proposed. Finally, the fiber fracture in various types of shotcrete is statistically analyzed. After correlation equation fitting, it is found that the straight-line, polynomial and exponential fitting results of mechanical properties and fiber fracture number of FRS are the most ideal. The relationship between the mechanical properties of FRS and the fiber fracture morphology is revealed. This study provides a theoretical basis for reducing the fractures of FRS structures in complex construction environments.